A regeneration-free high-efficiency carbon-containing aluminum defluorination agent and preparation method thereof
By preparing regeneration-free and efficient carbon-containing aluminum fluorine-removing agent under hydrothermal reaction conditions, the existing fluorine-removing adsorbents have been solved, and the efficient, low cost and environmentally friendly fluorine-removing effect has been achieved.
Patent Information
- Application Number
- CN202410174218.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-02-07
AI Technical Summary
The existing fluorine-removing adsorbents have small specific surface area, low adsorption capacity, are only suitable for acidic environments, are costly and require regeneration processes, resulting in increased costs and environmental pressures.
Regeneration-free high-efficiency carbon-containing aluminum fluorine-removing agent is used. The preparation method includes reacting sodium metaaluminate, nanooxide and low-molecular organic acid under hydrothermal reaction conditions, followed by washing and vacuum drying, and finally obtaining the fluorine-removing agent by pyrolysis.
The fluorine-deducting agent has a large specific surface area, efficient and rapid fluorine removal, low cost, and no regeneration, reducing operational complexity and environmental pollution risks.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection water treatment, and specifically relates to a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent and a preparation method thereof. Background Art
[0002] A moderate amount of fluoride is beneficial for tooth development and bone health, but long-term exposure can lead to fluorosis, kidney damage and even cancer. Fluoride mainly enters the human body through drinking water and food in nature. The fluoride content in drinking water is affected by the fluoride content in the earth's crust and industrial wastewater discharge. Compared with fluoride exposed alone, fluoride in drinking water is more harmful to human health. Therefore, defluoridation is the only feasible way to solve the problem of excessive fluoride in drinking water.
[0003] The main defluorination adsorbent that has been maturely applied is activated alumina. However, this product has problems such as small specific surface area, low adsorption capacity (generally less than 10 mg / g), only applicable to acidic environment, and high cost. In recent years, a mesoporous alumina has emerged as a defluorination adsorbent. Due to its large specific surface area, the adsorption and defluorination capacity is significantly improved, generally reaching more than 100 mg / g. However, the preparation process of this method is complicated, and usually requires the use of organic raw materials such as organic solvents, surfactants and alcohol aluminum, etc., and there are limitations such as toxic raw materials, environmental unfriendliness, and high cost. In addition, traditional adsorbents have problems with service life and regeneration, especially the regeneration process requires a large amount of chemical reagents, which increases costs and pollutes the environment.
[0004] Chinese patent CN113501599 discloses a method for treating fluorine-containing wastewater, comprising the following steps: (1) dissolving chitosan in an acid solution, adding a mixture powder consisting of coconut shell charcoal, diatomaceous earth and montmorillonite and stirring evenly, then adding an iron salt solution, adjusting the pH value of the solution, continuing to soak the obtained mixture and filtering it, washing the obtained solid with water, and drying the obtained solid to obtain a carboxylated chitosan combined with an iron salt modified adsorbent; adding a water-soluble aluminum source defluorinating agent to the fluorine-containing wastewater for ultrasonic oscillation defluorination reaction, and controlling the The pH value of the fluorine-containing wastewater during the reaction is adjusted to obtain a cryolite-containing mixed solution; the obtained cryolite-containing mixed solution is filtered to recover the cryolite, and then the chitosan-combined iron salt-modified adsorbent prepared in step (1) is added to the obtained filtrate and subjected to ultrasonic oscillation, and the modified adsorbent is filtered out; the provided method for treating fluorine-containing wastewater is prepared by a one-step hydrothermal method using common aluminum salts and inorganic reagents to synthesize economically valuable cryolite at room temperature, and then the adsorption method is used to reduce the fluorine concentration and impurity content, thereby meeting the wastewater recycling standard. However, considering that the defluorination adsorbent activated alumina widely used on the market has the problems of small specific surface area, low adsorption capacity, only applicable to acidic range, and high cost. Therefore, it is urgent to find a new and efficient defluorination adsorbent to achieve a breakthrough in defluorination technology. Summary of the invention
[0005] Technical issues solved:
[0006] This application aims at the deficiencies of the prior art, solves the technical problems of the prior art such as small specific surface area, low adsorption capacity, only applicable to acidic range, and high cost, and provides a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent and its preparation method, which can maintain good defluorination performance after long-term use, avoiding the cost and environmental pressure caused by the use of a large amount of chemical reagents in the regeneration process. At the same time, the defluoridation agent that does not require regeneration also reduces the complexity of operation, lowers the threshold for use, and is easier to promote and apply. By developing this new defluoridation adsorbent, the regeneration problem existing in the current adsorption method can be effectively solved, and a more feasible and sustainable solution is provided for the problem of excessive fluoride in drinking water, so as to solve the problems of complex preparation process of traditional adsorbents, low adsorption capacity, poor regeneration (currently there is no defluoridation agent on the market that does not require the use of regeneration liquid for analysis and regeneration), and the use of organic alcohol aluminum and polymer template reagents.
[0007] Technical solution:
[0008] To achieve the above objectives, this application is implemented through the following technical solutions:
[0009] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0010] Step 1: Weigh sodium aluminate dry powder: organic acid solution: nano oxide according to the mass volume ratio = 2-10g: 100ml: 2-5g, put the sodium aluminate dry powder and nano oxide in a beaker, add the organic acid solution, and stir for 30-150min;
[0011] Step 2: Pour the solution after stirring in step 1 into a hydrothermal reaction kettle and perform hydrothermal reaction at 140-240° C. for 1-5 hours;
[0012] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with distilled water, centrifuged again and washed once with ethanol, and centrifuged again and washed once with distilled water;
[0013] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 70-80°C;
[0014] Step 5: Place the sample vacuum-dried in step 4 into a muffle furnace for pyrolysis to obtain a regeneration-free, high-efficiency, carbon-containing aluminum defluorination agent.
[0015] As a preferred technical solution of the present application: the organic acid in step 1 is a low molecular weight organic acid, and the nano-oxide is an inorganic nano-particle.
[0016] As a preferred technical solution of the present application: the low molecular weight organic acid is one or more of acetic acid, propionic acid, benzoic acid, citric acid, and lactic acid; the inorganic nanoparticles are one or more of nano silicon oxide, nano magnesium oxide, and nano calcium oxide.
[0017] As a preferred technical solution of the present application: the stirring condition in step 1 is magnetic stirring or glass rod stirring.
[0018] As a preferred technical solution of the present application: the stirring speed in step 1 is 100 to 300 rpm.
[0019] As a preferred technical solution of the present application: the centrifugal speed in step 3 is 12000-16000 rpm, and the centrifugal time each time is 3-5 minutes.
[0020] As a preferred technical solution of the present application: the amount of ethanol or distilled water used for washing in step 3 is 40-50 ml.
[0021] As a preferred technical solution of the present application: the drying time in the vacuum drying oven in step 4 is 8 to 10 hours.
[0022] As a preferred technical solution of the present application: in the step 5, the pyrolysis conditions are under anoxic conditions, the temperature is 300-550° C., and the pyrolysis time is 1-5 hours.
[0023] The present application also discloses a regeneration-free and efficient carbon-containing aluminum defluorination agent prepared by any of the above-mentioned preparation methods.
[0024] Beneficial effects:
[0025] The present application provides a regeneration-free and efficient carbon-containing aluminum defluorination agent and a preparation method thereof, which has the following beneficial effects compared with the prior art:
[0026] 1. Simple synthesis: This technology adopts a simplified synthesis process, which reduces the complex steps and required raw materials in the preparation process, making the synthesis of the adsorbent simpler and more efficient, lowering the threshold for use and making it easier to promote and apply;
[0027] 2. Efficient and rapid fluorine removal: The new defluorinating agent has a large specific surface area and can provide more adsorption sites, thereby significantly improving the defluorination capacity. Its efficient adsorption speed can quickly remove fluoride from water and achieve rapid defluorination effect;
[0028] 3. Low cost: This technology uses economical and practical raw materials and simplified preparation process, which reduces the preparation cost of defluorination agent and makes it more commercially applicable;
[0029] 4. Non-toxic: The new defluoridation agent uses non-toxic raw materials, avoiding the potential toxicity problems of organic solvents and polymer template reagents that may exist in traditional defluoridation agents, ensuring the safety of water quality;
[0030] 5. No regeneration required: Unlike traditional defluoridation agents that need to be regenerated frequently, the defluoridation agent developed by this technology can continuously and effectively remove fluorine without regeneration, which reduces the complexity of operation and the cost of use, while avoiding the environmental pollution problems that may be caused by the regeneration process. This is a revolutionary technological breakthrough;
[0031] 6. Through the above characteristics, this technology can realize the preparation of efficient, rapid, low-cost and non-toxic defluoridation adsorbent, improve the defluoridation efficiency, and provide a feasible and sustainable solution to the problem of excessive fluoride in drinking water. DETAILED DESCRIPTION
[0032] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0033] Embodiment 1:
[0034] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0035] Step 1: Weigh sodium aluminate dry powder: acetic acid: nano-silicon oxide = 2g: 100ml: 5g according to the mass volume ratio, put the sodium aluminate dry powder and nano-silicon oxide in a beaker, add acetic acid solution, and stir with a magnetic stirrer or a glass rod at 100rpm for 30min;
[0036] Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 140°C for 1 hour;
[0037] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 40 ml of distilled water, centrifuged again and washed once with 40 ml of ethanol, and centrifuged again and washed once with 40 ml of distilled water; the centrifugal speed is 12000 rpm, and the centrifugal time for each time is 3 min;
[0038] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 70°C for 8 hours;
[0039] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 300°C and a pyrolysis time of 1 hour to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0040] Embodiment 2:
[0041] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0042] Step 1: Weigh sodium aluminate dry powder: propionic acid: nano calcium oxide = 2g: 100ml: 3g according to the mass volume ratio, put the sodium aluminate dry powder and nano calcium oxide in a beaker, add propionic acid solution, and stir with a magnetic stirrer or a glass rod at 100rpm for 30min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 140℃ for 1h;
[0043] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 40 ml of distilled water, centrifuged again and washed once with 40 ml of ethanol, and centrifuged again and washed once with 40 ml of distilled water; the centrifugal speed is 12000 rpm, and the centrifugal time for each time is 3 min;
[0044] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 70°C for 8 hours;
[0045] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 300°C and a pyrolysis time of 1 hour to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0046] Example 3
[0047] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0048] Step 1: Weigh sodium aluminate dry powder: benzoic acid: nano magnesium oxide = 2g: 100ml: 2g according to the mass volume ratio, put the sodium aluminate dry powder and nano magnesium oxide in a beaker, add benzoic acid, and stir with a magnetic stirrer or a glass rod at 100rpm for 30min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 140°C for 1h;
[0049] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 40 ml of distilled water, centrifuged again and washed once with 40 ml of ethanol, and centrifuged again and washed once with 40 ml of distilled water; the centrifugal speed is 12000 rpm, and the centrifugal time for each time is 3 min;
[0050] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 70°C for 8 hours;
[0051] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 300°C and a pyrolysis time of 1 hour to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0052] Embodiment 4:
[0053] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0054] Step 1: Weigh sodium aluminate dry powder: citric acid: nano-silicon oxide = 2g: 100ml: 5g according to the mass volume ratio, put the sodium aluminate dry powder and nano-silicon oxide in a beaker, add citric acid, and stir with a magnetic stirrer or a glass rod at 100rpm for 30min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 140°C for 1h;
[0055] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 40 ml of distilled water, centrifuged again and washed once with 40 ml of ethanol, and centrifuged again and washed once with 40 ml of distilled water; the centrifugal speed is 12000 rpm, and the centrifugal time for each time is 3 min;
[0056] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 70°C for 8 hours;
[0057] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 300°C and a pyrolysis time of 1 hour to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0058] Embodiment 5:
[0059] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0060] Step 1: Weigh sodium aluminate dry powder: lactic acid: nano calcium oxide = 2g: 100ml: 5g according to the mass volume ratio, put the sodium aluminate dry powder and nano calcium oxide in a beaker, add lactic acid solution, and stir with a magnetic stirrer or a glass rod at 100rpm for 30min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 140℃ for 1h;
[0061] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 40 ml of distilled water, centrifuged again and washed once with 40 ml of ethanol, and centrifuged again and washed once with 40 ml of distilled water; the centrifugal speed is 12000 rpm, and the centrifugal time for each time is 3 min;
[0062] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 70°C for 8 hours;
[0063] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 300°C and a pyrolysis time of 1 hour to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0064] Embodiment 6:
[0065] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0066] Step 1: Weigh sodium aluminate dry powder: acetic acid: nano calcium oxide = 10g: 100ml: 2g according to the mass volume ratio, put the sodium aluminate dry powder and nano calcium oxide in a beaker, add acetic acid solution, and stir with a magnetic stirrer or a glass rod at 300rpm for 150min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 240°C for 5h;
[0067] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 50 ml of distilled water, centrifuged again and washed once with 50 ml of ethanol, and centrifuged again and washed once with 50 ml of distilled water; the centrifugal speed is 16000 rpm, and the centrifugal time for each time is 5 min;
[0068] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry at 80°C for 10 hours;
[0069] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under anaerobic conditions at a temperature of 550°C and a pyrolysis time of 5 hours to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0070] Embodiment 7:
[0071] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0072] Step 1: Weigh sodium aluminate dry powder: acetic acid: nano magnesium oxide = 6g: 100ml: 5g according to the mass volume ratio, put the sodium aluminate dry powder and nano magnesium oxide in a beaker, add acetic acid solution, and stir with a magnetic stirrer or a glass rod at 200rpm for 90min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 190°C for 3h;
[0073] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 45 ml of distilled water, centrifuged again and washed once with 45 ml of ethanol, and centrifuged again and washed once with 45 ml of distilled water; the centrifugal speed is 14000 rpm, and the centrifugal time for each time is 4 minutes;
[0074] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry at 75°C for 9 hours;
[0075] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 450°C and a pyrolysis time of 3 hours to obtain a regeneration-free high-efficiency carbon-containing aluminum defluorination agent.
[0076] Embodiment 8:
[0077] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0078] Step 1: Weigh sodium aluminate dry powder: acetic acid: nano-silicon oxide = 4g: 100ml: 5g according to the mass volume ratio, put the sodium aluminate dry powder and nano-silicon oxide in a beaker, add acetic acid solution, and stir with a magnetic stirrer or a glass rod at 150rpm for 60min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 200℃ for 2h;
[0079] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 40 ml of distilled water, centrifuged again and washed once with 45 ml of ethanol, and centrifuged again and washed once with 50 ml of distilled water; the centrifugal speed is 13000 rpm, and the centrifugal time for each time is 3 min;
[0080] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 72°C for 8 hours;
[0081] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 350°C and a pyrolysis time of 2 hours to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0082] Embodiment 9:
[0083] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0084] Step 1: Weigh sodium aluminate dry powder: acetic acid: nano calcium oxide = 5g: 100ml: 3g according to the mass volume ratio, put the sodium aluminate dry powder and nano calcium oxide in a beaker, add acetic acid solution, stir with a magnetic stirrer or a glass rod at 250rpm for 120min; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor, and perform hydrothermal reaction at 200℃ for 4h;
[0085] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, and then washed once with 48 ml of distilled water, centrifuged again and washed once with 45 ml of ethanol, and centrifuged again and washed once with 42 ml of distilled water; the centrifugal speed is 15000 rpm, and the centrifugal time for each time is 4.5 min;
[0086] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry at 78°C for 9.5 hours;
[0087] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 500°C and a pyrolysis time of 4 hours to obtain a regeneration-free high-efficiency carbon-containing aluminum defluoridation agent.
[0088] Embodiment 10:
[0089] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0090] Step 1: Weigh sodium aluminate dry powder: acetic acid: nano-silicon oxide = 8g: 100ml: 4g according to the mass volume ratio, put the sodium aluminate dry powder and nano-silicon oxide in a beaker, add acetic acid solution, and stir with a magnetic stirrer or a glass rod at 280rpm for 140min;
[0091] Step 2: Pour the solution after stirring in step 1 into a hydrothermal reactor and perform hydrothermal reaction at 220°C for 4 hours;
[0092] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 50 ml of distilled water, centrifuged again and washed once with 45 ml of ethanol, and centrifuged again and washed once with 40 ml of distilled water; the centrifugal speed is 15000 rpm, and the centrifugal time for each time is 4.5 min;
[0093] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry at 78°C for 9 hours;
[0094] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 450°C and a pyrolysis time of 1 to 5 hours to obtain a regeneration-free high-efficiency carbon-containing aluminum defluorination agent.
[0095] Embodiment 11:
[0096] A method for preparing a regeneration-free high-efficiency carbon-containing aluminum defluorination agent specifically comprises the following steps:
[0097] Step 1: Weigh sodium aluminate dry powder: acetic acid: nano-silicon oxide = 9g: 100ml: 5g according to the mass volume ratio, put the sodium aluminate dry powder and nano-silicon oxide in a beaker, add acetic acid solution, and stir with a magnetic stirrer or a glass rod at 250rpm for 100min;
[0098] Step 2: Pour the solution after stirring in step 1 into a hydrothermal reaction kettle and perform hydrothermal reaction at 180°C for 2h;
[0099] Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with 40 ml of distilled water, centrifuged again and washed once with 45 ml of ethanol, and centrifuged again and washed once with 50 ml of distilled water; the centrifugal speed is 16000 rpm, and the centrifugal time for each time is 3 min;
[0100] Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 80°C for 8 hours;
[0101] Step 5: Place the sample vacuum dried in step 4 into a muffle furnace under oxygen-deficient conditions at a temperature of 400°C and a pyrolysis time of 1 to 5 hours to obtain a regeneration-free high-efficiency carbon-containing aluminum defluorination agent.
[0102] The experimental results of adsorption and defluorination of the non-regeneration high-efficiency carbon-containing aluminum defluoridation agent of the present application and the traditional alumina defluoridation agent show that the non-regeneration high-efficiency carbon-containing aluminum defluoridation agent of the present application has a removal rate of more than 95% for high-fluoride water with an initial fluoride concentration of 5-100 mg / L in the pH range of 3 to 10 at a dosage of 1 g / L, and its theoretical maximum adsorption capacity is 588.2 mg / g.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a regeneration-free carbon-containing aluminum defluorinating agent, characterized in that: The specific steps include: Step 1: Weigh sodium aluminate dry powder: organic acid solution: nano oxide = 2-10 g: 100 ml: 2-5 g according to the mass volume ratio, put the sodium aluminate dry powder and the nano oxide in a beaker, add the organic acid solution, and stir for 30-150 minutes; the organic acid is a low molecular organic acid, and the nano oxide is an inorganic nano particle; the low molecular organic acid is one or more of acetic acid, propionic acid, benzoic acid, citric acid, and lactic acid, and the inorganic nano particle is one or more of nano silicon oxide, nano magnesium oxide, and nano calcium oxide; Step 2: Pour the solution after stirring in step 1 into a hydrothermal reaction kettle and perform hydrothermal reaction at 140-240° C. for 1-5 hours; Step 3: After the hydrothermal reaction in step 2 is completed, the reactor is naturally cooled, the sample in the reactor is taken out and centrifuged, washed once with distilled water, centrifuged again and washed once with ethanol, and centrifuged again and washed once with distilled water; Step 4: Place the sample after three washes in step 3 in a vacuum drying oven and vacuum dry it at 70-80°C; Step 5: Place the sample vacuum-dried in step 4 into a muffle furnace for pyrolysis to obtain a regeneration-free carbon-containing aluminum defluorinating agent; the pyrolysis conditions in step 5 are anoxic conditions, the temperature is 300-550° C., and the pyrolysis time is 1-5 hours.
2. The method for preparing the regeneration-free carbon-containing aluminum defluorinating agent according to claim 1, characterized in that: The stirring condition in step 1 is magnetic stirring or glass rod stirring.
3. The method for preparing the regeneration-free carbon-containing aluminum defluorinating agent according to claim 1, characterized in that: The stirring speed in step 1 is 100-300 rpm.
4. The method for preparing the regeneration-free carbon-containing aluminum defluorinating agent according to claim 1, characterized in that: In step 3, the centrifugal speed is 12000-16000 rpm, and each centrifugation time is 3-5 min.
5. The method for preparing the regeneration-free carbon-containing aluminum defluorinating agent according to claim 1, characterized in that: In step 3, the amount of ethanol or distilled water used for washing is 40-50 ml.
6. The method for preparing the regeneration-free carbon-containing aluminum defluorination agent according to claim 1, characterized in that: The drying time in the vacuum drying oven in step 4 is 8 to 10 hours.
7. A regeneration-free carbon-containing aluminum defluorinating agent prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Metal oxide doped aluminum oxide as well as preparation and application thereof
CN108380170A
Carbon-doped aluminum-based adsorbent and preparation method thereof
CN116474736A